Increase of Reproductive Life Span Delays Age of Onset of Parkinson's Disease - Frentzel, Dominik; Judanin, Grigorij; Borozdina, Olga; Klucken, Jochen; Winkler, Jürgen; Schlachetzki, Johannes (Frontiers in Neurology, 2017)
One striking observation in Parkinson's disease (PD) is the remarkable gender difference in incidence and prevalence of the disease. Data on gender differences with regard to disease onset, motor and non-motor symptoms, and dopaminergic medication are limited. Furthermore, whether estrogen status affects disease onset and progression of PD is controversially discussed. In this retrospective single center study, we extracted clinical data of 226 ambulatory PD patients and compared age of disease onset, disease stage, motor impairment, non-motor symptoms, and dopaminergic medication between genders. We applied a matched-pairs design to adjust for age and disease duration. To determine the effect of estrogen-related reproductive factors including number of children, age at menarche, and menopause on the age of onset, we applied a standardized questionnaire and performed a regression analysis. The male to female ratio in the present PD cohort was 1.9:1 (147 men vs. 79 women). Male patients showed increased motor impairment than female patients. The levodopa equivalent daily dose was increased by 18.9% in male patients compared to female patients. Matched-pairs analysis confirmed the increased dose of dopaminergic medication in male patients. No differences were observed in age of onset, type of medication, and non-motor symptoms between both groups. Female reproductive factors including number of children, age at menarche, and age at menopause were positively associated with a delay of disease onset up to 30 months. The disease-modifying role of estrogen-related outcome measures warrants further clinical and experimental studies targeting gender differences, specifically hormone-dependent pathways in PD.
EVALuna2:36306